The Effect of Nickel Mass Variations on the Capacitance of Supercapacitor Electrodes Made of Graphite Nanoparticles - Hari Rahmadani; Reza Akbar Pahlevi; Soumen Mandal; Changiz Dehghanian; Shaymaa Hadi Al-Rubaye; Abolanle S. Adekunle; Ebru Koroglu (Frontier Advances in Applied Science and Engineering, 2025)
Energy storage based on energy and power density. Supercapacitors are one of the most promising types of energy storage device, because it has a higher energy density than dielectric capacitors and a higher power density than rechargeable batteries. In this study, Nickel and Graphite were used which were dissolved in Dimethyl Acetamide (DMAC) solvent. Ni/Graphite composites were characterized by XRD to determine the crystalline phase, SEM to determine morphology, and Charge-Discharge to determine electrochemical properties. XRD pattern analysis results, it was found that the highest intensity peak was at an angle of 26° and had a crystal size of 59.7 nm. Identification of SEM images on Ni/Graphite composites resulted in porosity of 71.4%, 71.8%, and 72%. Electrochemical performance of the electrode resulted in specific capacitance and optimum energy density at 20 %wt nickel mass variations of 71.8 Fg−1 and 69.65 Wh.Kg−1. The specific capacitance resulting from the Nickel/Graphite composite electrode is directly proportional to the addition of nickel mass.